Intermediality, life writing, and American studies interdisciplinary perspectives - Balestrini, Nassim Winnie; Bergmann, Ina (Buchreihe der Anglia / Anglia book series, 2018)
This collection of essays gathers innovative and compelling research on intermedial forms of life writing by an international and interdisciplinary group of scholars. Among their subjects of scrutiny are biographies, memoirs, graphic novels, performances, paratheatricals, musicals, silent films, movies, documentary films, and social media. The volume covers a time frame ranging from the nineteenth century to the immediate present. In addition to a shared focus on theories of intermediality and life writing, the authors apply to their subjects both firmly established and cutting-edge theoretical approaches from Cultural Narratology, Cultural History, Biographical Studies, Social Media Studies, Performance Studies, and Visual Culture Studies. The collection also features interviews with practitioners in biography who have produced monographs, films, and novels